The way west - Guthrie, A. B. 1901-1991 (W. Sloane Associates, 1949)
A hundred-odd men, women, and children gathered at the rendezvous a few miles outside of Independence. They were solid, established folk, most of them, and they were leaving behind prosperous farms and businesses because they shared a dream about the rich lands in the West, where a man, his wife, and their young ones might make a better life and a new world more desirable than any Americans before them had ever known.